Softer bodies - Pascual, Judith Ann Pia Sermona 1995-
"Softer Bodies is an auto-ethnographical documentary about Polycystic Ovarian Syndrome (PCOS). Softer Bodies is a personal documentary made by the filmmaker to better understand her condition - to release certain feelings of depression and confusion. Through video diaries, the filmmaker attempts to conver her relationship with her body, her relationship with her mind. Through a set of interviews, she realises the universality of the symptoms of the condition, as well as the certain nuances each person has. By interweaving the personal with the ethnographic, the film attempts to tell the story of PCOS, and how society values motherhood and physical appearances, and how women try to break or reinforce these stereotypes. Coupled with found footage and textured inserts, the filmmaker plays around with imagery, including footage of herself. The filmmaker hopes to open discussions on health, body image, and motherhood - by asking the question: how can you give off yourself without fear, without losing yourself?"